KAJIAN STRATEGI PENGEMBANGAN PERKEBUNAN PISANG KEPOK SEBAGAI KOMODITAS UNGGULAN DI KABUPATEN SERUYAN KALIMANTAN TENGAH - Permadi, Rokhman; Winarti, Lili (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Promoting the development of kepok banana plantations is an effort to strengthen domestic food security and significantly contribute to the economy. The main objective of this research is to offer several strategies for developing kepok banana plantations in Seruyan Regency. This research is based on various empirical analyses, including questionnaires and interviews with kepok banana farmers in three central villages of kepok banana plantations in Seruyan Regency, namely Sungai Bakau Village, Pematang Panjang Village, and Bangun Harja Village. To achieve these objectives, a strengths, weaknesses, opportunities, and threats (SWOT) approach was used, and based on the results, a quantitative strategic planning matrix (QSPM) approach was employed to manage the kepok banana plantations effectively. The research findings indicate weaknesses such as using simple technology by farmers, limited farmer group activities, lack of capital, limited knowledge of the market system, and weak farmer institutions. On the other hand, there are also several opportunities such as the development of information and communication technology, relatively secure farming activities with low crime rates, policies on food diversification, high demand for bananas, sufficient available land, and available labor force. Therefore, the current development strategy emphasizes the need to strengthen farmer organizations, optimize existing farmland to increase production, and seek government assistance as a high-priority alternative strategy for the location's kepok banana plantations.